2022
DOI: 10.1021/acsnano.2c04377
|View full text |Cite
|
Sign up to set email alerts
|

Communication Breakdown: Into the Molecular Mechanism of Biofilm Inhibition by CeO2 Nanocrystal Enzyme Mimics and How It Can Be Exploited

Abstract: Bacterial biofilm formation is a huge problem in industry and medicine. Therefore, the discovery of anti-biofilm agents may hold great promise. Biofilm formation is usually a consequence of bacterial cell–cell communication, a process called quorum sensing (QS). CeO2 nanocrystals (NCs) have been established as haloperoxidase (HPO) mimics and ecologically beneficial biofilm inhibitors. They were suggested to interfere with QS, a mechanism termed quorum quenching (QQ), but their molecular mechanism remained elus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…Thus, the bromination of phenol red to tetrabromophenol blue does not proceed. We do not show here again the biofilm inhibiting properties of the PES–BiCe–CaO 2 composites, because this has already been reported before for CeO 2 /paint, 26 Bi 0.2 CeO 1.9 O 1.95 /PES, 36 CeO 2 /polyurethane 54 or CeO 2− x /polycarbonate 61,62 composites.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, the bromination of phenol red to tetrabromophenol blue does not proceed. We do not show here again the biofilm inhibiting properties of the PES–BiCe–CaO 2 composites, because this has already been reported before for CeO 2 /paint, 26 Bi 0.2 CeO 1.9 O 1.95 /PES, 36 CeO 2 /polyurethane 54 or CeO 2− x /polycarbonate 61,62 composites.…”
Section: Resultsmentioning
confidence: 49%
“…Likewise, no oxidative bromination occurred in the absence of H 2 O 2 , i.e., peroxide is essential for the initiation of the reaction. The porous structure of the polymer beads facilitates the diffusion of dissolved ionic or low molecular reactants (i.e., signaling compounds for quorum quenching of bacteria [13][14][15]54 ) through the polymer and ensures that the catalytic haloperoxidase-like reaction always proceeds. So, the idea is similar to that of modern drug delivery systems, where drugs are released from nanoparticles or polymer capsules.…”
Section: Synthesis and Characterization Of Pes And Pvdf Nanocompositesmentioning
confidence: 99%
“…TP301 could be confirmed by an in-house synthesized standard (Table S5 of the Supporting Information). Further details were reported by Pütz et al…”
Section: Resultsmentioning
confidence: 99%
“…However, the influence of cerium dioxide NCs on QSMs is not fully understood. Pütz et al showed that the communication molecules C 4 -AHL and 3-OH-C 10 -AHL were not degraded from cerium dioxide NCs, but the long-chain AHL 3-Oxo-C 12 -AHL and N -Oxo-2-heptyl-4-quinolone (HQNO), a quinolone-like HHQ, can be catalytically brominated and transformation products (TPs) were identified. Michels et al showed the halogenation of short-chain AHL 3-Oxo-C 6 -AHL for active halogen and proposed a transformation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…QS primarily regulates collective features that involve energetically costly “public goods” and are most effective or even only functional if performed by a microbial consortium. Bacterial traits controlled by QS include genetic phenotypes, biofilm formation, promoting or inhibiting function, and virulence ( Mashruwala et al, 2022 ; Pütz et al, 2022 ; Ramsay et al, 2022 ). QS even can be a driver and target of other functions ( Striednig and Hilbi, 2022 ).…”
Section: Construction Strategy Of Microbial Consortia For Degradationmentioning
confidence: 99%